2012
DOI: 10.1590/s1413-86702012000300012
|View full text |Cite
|
Sign up to set email alerts
|

Assessing subtypes and drug resistance mutations among HIV-1 infected children who failed antiretroviral therapy in Kelantan, Malaysia

Abstract: A b s t r A c t Antiretroviral (ArV) therapy has dramatically reduced morbidity and mortality in human immunodeficiency virus 1 (HiV-1) infected children. However, development of ArV resistance in these children is a major public health problem due to lack of availability of and access to new drugs. this study was conducted in order to identify circulating HiV subtypes and recombinant forms and evaluate the drug resistance mutation patterns in 18 HiV-1 infected children failing ArV treatment in Kelantan, Malay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 6 publications
2
12
0
Order By: Relevance
“…The prevalence of HIV in our study is remarkable because it exceeds the high (12z) prevalence of HIV among female sex workers in Surabaya (6). The genomic fragment of CRF01_AE has been identified as the predominant HIV-1 subtype in South East Asia, including Malaysia, Thailand, and Taiwan (43)(44)(45) as well as Jakarta, Surabaya, and Bali in Indonesia (6,46). Our results are consistent with those of previous findings.…”
supporting
confidence: 91%
“…The prevalence of HIV in our study is remarkable because it exceeds the high (12z) prevalence of HIV among female sex workers in Surabaya (6). The genomic fragment of CRF01_AE has been identified as the predominant HIV-1 subtype in South East Asia, including Malaysia, Thailand, and Taiwan (43)(44)(45) as well as Jakarta, Surabaya, and Bali in Indonesia (6,46). Our results are consistent with those of previous findings.…”
supporting
confidence: 91%
“…However, in 2007, a rapid expansion of CRF33_01B in Kuala Lumpur was observed, suggesting a possible replacement of predominant subtypes in near future [17]. Interestingly, in 2012, Mohamad et al (2012) [8] reported that 44.4% of pediatric patients harboured subtype CRF33_01B. The following year, CRF33_01B was found to be highly prevalent among drug users (71%) [18].…”
Section: Discussionmentioning
confidence: 99%
“…Viral RNA extraction, reverse transcriptase-PCR (RT-PCR), and nested PCR were performed as previously described [8]. Nucleotide sequences of PR and RT regions were edited, aligned, and analyzed for drug resistance using the Stanford HIV Resistance Database (http://hivdb.stanford.edu/).…”
Section: Genotypic Resistance Assessmentmentioning
confidence: 99%
“…When accompanied by other TAMs, it leads to reduced susceptibility to Abacavir (ABC), Didanosine (DDI), and Tenofovir (TDF). D67E is a non-polymorphic mutation that generally occurs in viruses with multiple TAMs [16,17].…”
Section: Surveillance Drug-resistant Mutations and Hiv-1 Subtypes In mentioning
confidence: 99%